2022
DOI: 10.1002/jcsm.12920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protocol‐based physiotherapy on insulin sensitivity and peripheral glucose metabolism in critically ill patients

Abstract: Background The impact of physiotherapy on insulin sensitivity and peripheral glucose metabolism in critically ill patients is not well understood. Methods This pooled analysis investigates the impact of different physiotherapeutic strategies on insulin sensitivity in critically ill patients. We pooled data from two previous trials in adult patients with sequential organ failure assessment score (SOFA)≥ 9 within 72 h of intensive care unit (ICU) admission, who received hyperinsulinaemic euglycaemic (HE) clamps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Not only in chronic disease, but also in acute conditions of critical illness, insulin resistance has been linked to impaired mitochondrial biogenesis [ 180 ]. The phenomenon of insulin resistance was highlighted as a metabolic hallmark feature in critical illness myopathy and ICUAW [ 90 , 181 , 182 ]. Furthermore, overall gastrointestinal function may be impaired especially in critically ill patients with neuromuscular alterations [ 183 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Not only in chronic disease, but also in acute conditions of critical illness, insulin resistance has been linked to impaired mitochondrial biogenesis [ 180 ]. The phenomenon of insulin resistance was highlighted as a metabolic hallmark feature in critical illness myopathy and ICUAW [ 90 , 181 , 182 ]. Furthermore, overall gastrointestinal function may be impaired especially in critically ill patients with neuromuscular alterations [ 183 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
“…Therefore, impairments of AKT-mediated FOXO suppression in critical illness may directly hamper mitochondrial function and promote muscle wasting. Furthermore, insulin-independent translocation of GLUT4 via activated AMPK was shown to be diminished in CIM patients [ 78 , 182 ]. The AMPK is another enzyme interlinking glucose metabolism, mitochondrial function and skeletal muscle integrity.…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
“…Early protocol-based mobilization has been shown to improve functionality and counteract muscle atrophy as well as insulin resistance [ 6 , 8 , 9 ]. Nevertheless, evidence has not always been uniform and some studies failed to demonstrated the association [ 10 ]. Although controversial, intensive insulin therapy has been shown to have a protective effect regarding the development of neuromuscular dysfunction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%